Perceived stigma among undergraduate medical students towards people with psychiatric illness: A cross sectional study - Amar Deep Patel; Maha Prakash Sharma; Alok Pal; Upendra Kumar Verma; Paritosh Tiwari; Zaryab Alam (Journal of Family Medicine and Primary Care)
Background: Over 450 million individuals worldwide suffer from mental illnesses, according to epidemiological data, making this one of the biggest problems facing modern medicine. People often react in a fairly discriminatory way to those with mental illness, and stigmatizing views toward those with mental illness are ubiquitous. In India, people who suffer from mental illness live with their families, and the stigma associated with mental illness has a significant impact on how effectively these people are treated over time by their families and communities. Objective: This study aims to specifically investigate how undergraduate medical students who participated in a two-week psychiatric posting and teaching program and those who did not learn about mental illness from the course curriculum or clinical experience differed in their perceived stigma toward people with mental illness. Materials and Methods: This cross-sectional study used a self-reported Perceived devaluation-discrimination scale (PDDS) questionnaire distributed via Google form to undergraduate medical students who were exposed (n = 72) to a two-week psychiatry posting and attended lectures and those who were not exposed (n = 176) to psychiatry training. Results: The results show that medical students’ perceptions of the stigma associated with mental illness remain unchanged following their exposure to psychiatry training. Nonetheless, it was discovered that students’ perceptions of the stigma associated with mental health patients were influenced by their urban domicile. Conclusions: Our research indicates that there was perceived stigma among medical students about patients with mental illnesses, and that this tendency was more pronounced among students belonging from rural areas.